Smart Parking System - et. al., J. Harirajkumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we proposed a smart parking system to detecting the parking area for the customers. Due to increase of vehicle density particularly in peak hours it is difficult to finding and parking their cars. The purpose of our paper is a Smart parking system with the parking system with the help of Arduino components. The level of traffic congestion increases with the increasing of population rapidly. The traffic congestion occurred due to more number of car users. This Smart parking system is used to show their parking area accurately with the help of OLED display. It avoid unnecessary time consuming to finding their parking space. This system will overcomes a problem like parking offences and fine. We create a system which helps the people to know their parking slot for vehicles.